SIMULATION MODELING OF NETWORK CHANNELS WITH QUEUES OF PROTECTED INFORMATION PACKETS - Kolyada, M. G. (Radio Electronics, Computer Science, Control, 2024)
In the paper the gear of optimization of network’s channels with sequential queues of packets of the protected information on the basis of simulation modeling is represented. The solution of a specific target is adduced in view of probability and cumulative distribution function arriving, protected packets to one channel.